Bi‐based photocatalysts for light‐driven environmental and energy applications: Structural tuning, reaction mechanisms, and challenges. Issue 3 (7th September 2020) - Chen, Peng; Liu, Hongjing; Cui, Wen; Lee, Shun Cheng; Wang, Li'ao; Dong, Fan
Abstract: Environmental pollution and energy crisis have become major challenges to sustainable development of human society. Solar‐driven photocatalytic technology is regarded as an extremely attractive solution to environmental remediation and energy conversion. Unfortunately, practical applications of traditional photocatalysts are restricted owing to the poor absorption of visible light, insufficient charge separation and undefined reaction mechanism. Therefore, developing novel visible light photocatalysts and exploring their modification strategies are significant in the area of photocatalysis. Bi‐based photocatalysts have attracted wide attention due to unique geometric structures, tunable electronic structure and decent photocatalytic activity under visible light. At present, Bi‐based photocatalysts can be mainly classified as bismuth metal, binary oxides, bismuth oxyhalogen, multicomponent oxides and binary sulfides, and so forth. Although they can be used as independent photocatalysts for environmental purification and energy development, their efficiency is not ideal. Therefore, many efforts have been made to enhance their photocatalytic performance in the past few decades. Significant progresses in determining the fundamental properties of photocatalysts, improving the photocatalytic performance and understanding the photocatalytic mechanism in important reactions have been made benefited from the various new developed concepts and approaches. This review introduces the structural properties of Bi‐based photocatalysts in detail and summarizes the design and modification strategy for improving the photocatalytic performance, including metal/nonmetal doping, construction of heterojunctions, regulation of crystal facet exposure, and structural defects. Furthermore, we discuss the catalysis mechanisms of Bi‐based materials in terms of semiconductor photocatalysis and plasmonic photocatalysis. Finally, the applications, challenges and prospects of Bi‐based photocatalysts are proposed to guide the future work. Abstract : Bi‐based photocatalysts have attracted wide attention due to unique geometric structures, tunable electronic structure and decent photocatalytic activity under visible light. This review introduces the structural properties of Bi‐based photocatalysts in detail and summarizes the design and modification strategy for improving the photocatalytic performance, including metal/nonmetal doping, construction of heterojunctions, regulation of crystal facet exposure, and structural defects. Furthermore, the catalysis mechanisms of Bi‐based materials in terms of semiconductor photocatalysis and plasmonic photocatalysis are also discussed. Finally, the applications, challenges and prospects of Bi‐based photocatalysts are proposed to guide the future work.